ICOMOS - (:unkn) unknown (My University, 2026)
ICOMOS, the International Council on Monuments and Sites, is a global non-governmental organization associated with UNESCO. Its mission is to promote the conservation, protection, use and enhancement of monuments, building complexes and sites. It participates in the development of doctrine and the evolution and distribution of ideas, and conducts advocacy. ICOMOS is an Advisory Body of the World Heritage Committee for the implementation of the World Heritage Convention of UNESCO. As such, it reviews the nominations of cultural world heritage and ensures the conservation status of properties. Its creation in 1965 is the logical outcome of initial conversations between architects, historians and international experts that began in the early twentieth century and that materialized in the adoption of the Venice Charter in 1964. In light of numerous studies, conferences, symposia and discussions led by its National Committees and International Scientific Committees, ICOMOS has gradually built the philosophical and doctrinal framework of heritage on an international level.